Inclusive development and multilevel transboundary water governance : the Kabul River - Hayat, Shakeel (Leiden : CRC Press/Balkema, 2020)
The four decades long ideological-based insurgencies and conflict in the Kabul River Basin (KRB) have seriously hampered the relations and foreign policies of both Afghanistan and Pakistan. Consequently, it restricts them to solve various bilateral issues including transboundary waters. This lack of cooperation over shared water resources is one of the barriers to achieve inclusive and sustainable development. Additionally, it has contributed to the prevailing anarchic situation where each country does what it wants. The absence of a formal water-sharing mechanism coupled with poor water management practices within both the riparian counties are resulting various flow and administration-related challenges. Moreover, these challenges are further exacerbated by regional changes in social, political, environmental and economic systems. The scholarly literature suggests that an analytical transboundary water governance framework is essential to address the challenges of water politicisation and securitisation, quality degradation and quantity reduction. Additionally, the literature rarely integrates (a) a multi-level approach, (b) an institutional approach (c) an inclusive development approach, or (d) accounts for the uses of different types of water and their varied ecosystem services for improved transboundary water governance. To enhance human wellbeing and achieve inclusive and sustainable development in the KRB this research indicates that it is essential to: (1) defrost frozen collaboration; (2) bypass border dispute; (3) use biodiversity and ecosystem services approach; (4) address existing and potential natural and anthropogenic challenges; (5) remove contradictions in the policy environment; (6) combat resource limits and dependence by promoting collaboration on long-term cost effective solutions; and (7) enhance knowledge and dialogue on inclusive development.
1 INTRODUCTION 1.1 INTRODUCTION 1.2 REAL LIFE ISSUES 1.3 THEORETICAL GAPS IN TRANSBOUNDARY WATER GOVERNANCE LITERATURE 1.4 MAIN RESEARCH QUESTION AND SUB-QUESTIONS 1.5 FOCUS AND LIMITS 1.6 LIMITS OF THE THESIS 1.7 STRUCTURE OF THE THESIS 2 METHODOLOGY AND ANALYTICAL FRAMEWORK 2.2 LITERATURE REVIEW 2.3 CONTENT ANALYSIS2.4 CHOICE OF CASE STUDY 2.5 THE CONCEPTUAL APPROACH 2.6 INTEGRATED INSTITUTIONAL ANALYSIS 2.7 KEY LIMITATIONS OF THE THESIS2.8 RESEARCH ETHICS 3 APPROACHES TO TRANSBOUNDARY WATER GOVERNANCE 3.1 INRODUCTION 3.2 INTERNATIONAL RELATIONS (IR) APPROACHES IN TRANSBOUNDARY GOVERNANCE 3.3 Hydro Hegemony (HH) 3.4 WATER GOVERNANCE AND INSTITUTIONS 3.5 THE INTERRELATED ROLE OF POWER AND INSTITUTIONS 3.6 CONCLUSION 4 ECOSYSTEM SERVICES AND HUMAN WELL-BEING 4.1 INTRODUCTION 4.2 DRIVERS OF FRESHWATER PROBLEM AT MULTIPLE LEVELS 4.3 FRESHWATER AND ITS TYPES 4.4 ECOSYSTEM SERVICES OF DIFFERENT KINDS OF FRESHWATER 4.5 ECOSYSTEM SERVICES AND HUMAN-WELLBEING 4.6 INFERENCES 5 GLOBAL WATER INSTITUTIONS AND ITS RELATIONSHIP WITH INCLUSIVE AND SUSTAINABLE DEVELOPMENT 5.1 INTRODUCTION 5.2 OVERVIEW OF GLOBAL WATER INSTITUTIONS 5.3 KEY GLOBAL WATER GOVERNANCE INSTITUTIONS 5.4 INVENTORY OF KEY PRINCIPLES IN GLOBAL WATER INSTITUTIONS 5.5 ROLE OF RIVER BASIN ORGANISATIONS IN DISPUTE RESOLUTION 5.6 INFERENCES 6 ANALYSIS OF INTERNATIONAL RELATIONS IN THE KABUL RIVER BASIN (KRB) 6.1 INTRODUCTION 6.2 THE CONTEXT OF WATER GOVERNANCE AT TRANSBOUNDARY LEVEL IN THE KRB 6.3 CHARACTERISTICS AND ECOSYSTEM SERVICES OF THE KRB 6.4 DRIVERS OF FRESHWATER PROBLEMS AT TRANSBOUNDARY LEVEL IN THE KRB 6.5 EVOLUTION OF TRANSBOUNDARY LEVEL INSTITUTIONS & PRACTICES IN THE KRB 6.6 GOALS, PRINCIPLES AND INSTRUMENTS 6.7 POWER ANALYSIS OF THE KRB RIPARIAN STATES IN TERMS OF GEOGRAPHIC AND THREE ELEMENTS OF POLITICAL POWER 6.8 INFERENCES 7 ANALYSIS OF WATER GOVERNANCE IN AFGHANISTAN 7.1 INTRODUCTION 7.2 THE CONTEXT OF WATER GOVERNANCE IN AFGHANISTAN 7.3 ECOSYSTEM SERVICES OF FRESHWATER IN AFGHANISTAN 7.4 DRIVERS OF FRESHWATER PROBLEMS AT NATIONAL & SUB- NATIONAL LEVEL IN AFGHANISTAN 7.5 EVOLUTION OF THE FRESHWATER & RELATED INSTITUTIONS IN AFGHANISTAN 7.6 GOALS, PRINCIPLES AND INSTRUMENTS 7.7 LEGAL PLURALISM ANALYSIS 7.8 PRINCIPLES & INSTRUMENTS ADDRESSING DRIVERS & ACHIEVING INCLUSIVE & SUSTAINABLE DEVELOPMENT 7.9 POWER ANALYSIS OF FRESHWATER GOVERNANCE IN AFGHANISTAN 7.10 INFERENCES 8 ANALYSIS OF MULTILEVEL FRESHWATER GOVERNANCE IN PAKISTAN 8.1 INTRODUCTION 8.2 THE CONTEXT OF WATER GOVERNANCE WITHIN PAKISTAN 8.3 ECOSYSTEM SERVICES OF FRESHWATER IN PAKISTAN 8.4 DRIVERS OF FRESHWATER PROBLEMS IN PAKISTAN 8.5 EVOLUTION OF THE FRESHWATER AND RELATED INSTITUTIONS IN PAKISTAN 8.6 GOALS, PRINCIPLES AND INSTRUMENTS 8.7 LEGAL PLURALISM ANALYSIS 8.8 PRINCIPLES & INSTRUMENTS ADDRESSING DRIVERS & ACHIEVING INCLUSIVE & SUSTAINABLE DEVELOPMENT 8.9 HOW DO POWER AND INSTITUTIONS INFLUENCE WATER SHARING IN PAKISTAN? 8.10 INFERENCES 9 MULTI-LEVEL INTEGRATED ANALYSIS FOCUSING ON ISSUES FOR RE-DESIGN 9.1 INTRDUCTION 9.2 THE CONTEXT OF MULTILEVEL WATER GOVERNANCE IN THE KRB 9.3 MULTILEVEL BIODIVERSITY AND ECOSYSTEM SERVICES IN THE KRB 9.4 THE MULTILEVEL DRIVERS OF CONFLICT 9.5 GOALS, PRINCIPLES AND INSTRUMENTS IN MULTILEVEL GOVERNANCE FRAMEWORKS 9.6 THE MULTILEVEL LEGAL PLURALISM ANALYSIS 9.7 APPLICABILITY OF ARTICLE 5 AND 6 FOR ENHANCING MULTILEVEL WATER GOVERNANCE IN THE KRB 9.8 INFERENCES 10 CONCLUSION 10.1 INTRODUCTION 10.2 RECALLING THE QUESTIONS 10.3 CONCLUSIONS AND RECOMMENDATIONS 10.4 CAN PAKISTAN USE HEGEMONIC STABILITY THEORY TO PROMOTE WATER RELATED PEACE? 11 REFERENCES ANNEX A: Thesis Log Frame ANNEX B: Keywords searched in scientific databases ANNEX C: List of people interviewed ANNEX D: List of constitutions, water laws & policies in Afghanistan ANNEX E: List of constitutions, water laws and policies in Pakistan ANNEX F: List of transboundary laws, proposal and discussions in the KRBANNEX G: Evolution of transboundary-level formal/informal water governance frameworks in the KRB ANNEX H: Evolution of water governance frameworks in Afghanistan ANNEX I: Evolution of freshwater governance frameworks from national to local level in Pakistan ANNEX J: Major principles & instruments in Pakistan's multilevel water governance fameworks ANNEX K: Multilevel ecosystem services in the KRB
Originally presented as author's thesis (Ph.D.)--Universiteit van Amsterdam.
OCLC-licensed vendor bibliographic record.
Keywords: Water-supply -- Government policy -- Afghanistan; Water-supply -- Government policy -- Pakistan; Water security -- Afghanistan; Water security -- Pakistan; Kabul River (Afghanistan and Pakistan); SCIENCE / Environmental Science; TECHNOLOGY / Engineering / Civil